1999
DOI: 10.1111/j.1346-8138.1999.tb02093.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic Analysis of 124 Cases of Adult T‐Cell Leukemia/Lymphoma with Cutaneous Manifestations: The Smouldering Type with Skin Manifestations Has a Poorer Prognosis than Previously Thought

Abstract: Adult T-cell leukemia/lymphoma (ATLL) commonly involves the skin as well as peripheral blood and lymph nodes. During the last 15 years we have studied 124 cases of ATLL with specific skin manifestations. Twenty-one patients (16.9%) were classified as acute, 21 (16.9%) as chronic, 26 (21.0%) as lymphoma, and 56 (45.2%) as smouldering according to Shimoyama's classification. Many patients had nodules/tumors (34.7%), erythematous plaques (22.6%), and erythematous papules (19.4%) similar to those occurring with ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
66
5
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(81 citation statements)
references
References 9 publications
6
66
5
4
Order By: Relevance
“…In addition, patients with primary cutaneous smoldering ATL mostly died of infections or of causes not directly related to ATL. The MST observed in this study for the primary cutaneous smoldering ATL was higher than those reported by Setoyama et al (1999) [30]. Provably this difference may be due to different criteria used by these authors.…”
Section: Discussioncontrasting
confidence: 55%
“…In addition, patients with primary cutaneous smoldering ATL mostly died of infections or of causes not directly related to ATL. The MST observed in this study for the primary cutaneous smoldering ATL was higher than those reported by Setoyama et al (1999) [30]. Provably this difference may be due to different criteria used by these authors.…”
Section: Discussioncontrasting
confidence: 55%
“…Some previous studies suggested that skin involvements might be a risk factor for poor prognosis of smoldering ATL. 6,[20][21][22] In the present study, the frequency of patients with skin lesion was a little higher in smoldering ATL (n ϭ 14; 56%) than in chronic ATL (n ϭ 32; 49%). The OS of smoldering ATL with skin lesion was worse than that of chronic ATL without skin lesion (supplemental Figure 2), although there was no statistical difference (P ϭ .5).…”
Section: Discussionmentioning
confidence: 78%
“…However, some studies reported that the presence of skin lesions was a possible poor prognostic factor in indolent ATL, 6,20-22 as described earlier. Setoyama et al 21 reported that smoldering cases with a deeper infiltration pattern had a more aggressive course than cases with a superficial infiltration pattern. Degree of skin involvement might be associated with prognosis in indolent ATL.…”
Section: Discussionmentioning
confidence: 99%
“…Most patients present with acute ATLL characterized by the presence of leukemia, lymphadenopathy, organomegaly, hypercalcemia, and in about 50% skin lesions, most commonly nodules or tumors (33%), generalized papules (22%), or plaques (19%). 96 Chronic and smoldering variants frequently present with skin lesions, which may closely resemble MF, whereas circulating neoplastic T cells are few or absent.…”
Section: Sé Zary Syndromementioning
confidence: 99%